Improving Quality Systems in Local Pharmaceutical Manufacturing: Using Analytical Hierarchy Process - Alexandor, Robert Paul (1997)
The primary objective of this research was to identify and address the factors involved in overall quality production of ER Pharmaceutical products. A second objective was to be operationlise. These factors with the system, "cetirus parebus" that enable a company to shift from one with lower level of quality skills to one that would be in line with the call of "Quality 2020". As expected the two factors come to the fore: - a) quality products b) the ability to use quality to meet the needs and satisfaction of customers. Internal and external customers were assessed by Analytical Hierarchy Process Survey techniques to assess the needs and identify factors in this study. Questionnaires were issued and return monitored. The two objectives was to collect data as integrated factors of Product Quality and Human Resources factors involved in Human Resources related to product quality. There were thirteen product quality factors selected for this research: 1) Visual appearance, 2) Friability 3) Disintegration 4) Taste 5) packaging 6) Embossing 7) Hardness . The human Resource factors included in this paper were 1) willingness to change 2) Knowledge 3) Skill 4) Commitment 5) Attitude 6) Teamwork and 7) leadership. Analytical Hierarchy Process was undertaken to facilitate ranking procedures. The subsequent ranking for product quality was 1) Strip Packing 2) uneven color, 3) Visual appearance 4) Friability 5) Texture 6) Blister Packing 7) Disintegration 8) Taste 9) Crack 10) Packaging 11) shape 12) Embossing and 13) Hardness Th final ranking of the human resources factors was 1) Willingness to Change 2) Knowledge 3) Skill 4) Commitment 5) Attitude 6) Teamwork and 7) Leadership. It was found that it was vital for process Engineers to consider the identified factors and accord them with fundamental importance in establishing high quality process function. Participation and input from Human resources was also gauged as important factor in determining High Quality. HR participation is the transformation of personnel as vital ingredients in successful output.